Problem Based Learning Berbantuan Audio Visual terhadap Kemampuan Berpikir Kritis Siswa SD - Anita Rachman Ainur Rofiqoh; Meirza Nanda Faradita; Kunti Dian Ayu Afiani (Universitas Pendidikan Indonesia (UPI), 2023)
This study aims to determine the effect of audio-visual assisted PBL on the critical thinking of grade V elementary school students in science subjects at MI Muhammadiyah 5 Surabaya. This research uses Quantitative research methods with the type of research used, namely pre-experimental research (Pre-experiment). The design used by researchers is the One Group Pretest-Posttest Design with one class as the subject of research. Data analysis techniques in this study are a normality test and one sample T-test using the one sample test method with the help of SPSS. The results showed that the data analysis of one sample T-test using the one sample T technique shows a significance value of 0.05 at 0.0 00. So it can be concluded that the audio-visual assisted PBL model affects the critical thinking skills of elementary school students.